Protocol to assess the effects of dysfunctional human vascular smooth muscle cells on other brain cells using in vitro models of Alzheimer’s disease - Karla Lucia F. Alvarez; Jorge Aguilar-Pineda; Karin J. Vera-Lopez; Christian L. Lino Cardenas (STAR Protocols, 2022)
Summary: Here, we present a protocol to culture primary human vascular smooth muscle cells (VSMCs) under Alzheimer's disease (AD)-like conditions, including steps for morphological characterization with microscopy. We then describe functional assays, including wound healing, transwell, coculture, and supernatant assays, to evaluate the effect of dysfunctional VSMCs on the induction of the AD-associated microglial phenotype. Our approach can be applied to assess the effects of dysfunctional VSMCs on other cerebral cell lines including pericytes, astrocytes, and neurons under AD-like conditions in vitro.For complete details on the use and execution of this protocol, please refer to Aguilar-Pineda et al. (2021).